Evaluation of the Effect of Periodontal Treatments on Insulin Resistance Diabetic Patients with Periodontitis - Narges Naghsh; Samaneh Soltani; Jaber Yaghini; Saman Abolfazli (Isfahan University of Medical Sciences, 2023)
The purpose of present study was to evaluate the effect of periodontal treatments on insulin resistance and periodontal indices in diabetic patients with chronic periodontitis based on blood glucose control in Isfahan dental faculty in years 2015-2016.Materials & Methods:This single blinded controlled clinical trial was conducted on 60 patients referred to Khoram treatment center and Isfahan dental facultyin 2015-16. Patients were divided into four groups based on blood sugar control.Before treatment, periodontal indices were measured, and insulin resistance was detected by measuring of salivary resisting. Then phase 1 of periodontal treatment was performed andfollowing three months the mentioned indices were measured again. Finally, the data was analyzed with a one-way analysis of variance test, Tukey's Post Hoc Test and paired sample t-test. The significance level was set at α = 0.05.Results:The results showed that average of glycated hemoglobin, pocket depth, percentage of areas with bleeding and plaque index had a significant difference before and after treatment in each of the four groups p value < 0.05, although the mean changes between groups were notsignificant (45, 58, 19 & 48%).Conclusion:Non-surgical periodontal treatment improves periodontal indices and reduces glycated hemoglobin and salivary resistin, however there was no association between severity of diabetes and the mentioned indices.